Capital and lending growth of banking sector in Indonesia: Study on the BUKU category - Ahmad Aziz Putra Pratama (Jurnal Keuangan dan Perbankan, 2019)
Mostly, loans are an essential source of income for banks, and capital is used to absorb shocks during default risk. This study examines the effect of bank capital on lending growth in each Commercial Bank based on Business Activities (BUKU) category listed on the Indonesia Stock Exchange (IDX). This research used the fixed effect model. Data obtained from the company's financial report published in the 2010-2016 period. There is an inconsistency effect of bank capital on lending growth in each category. The results showed that bank capital has a significant positive effect on lending growth at all bank samples, BUKU 1, and BUKU 2. Furthermore, bank capital has a significant negative effect on lending growth at BUKU 3 and BUKU 4. Analysis results showed that behavioral lending differs based on their owned core capital. This study implied that BUKU 1 and BUKU 2 tend to implement aggressive strategies to deal with market competition, while BUKU 3 and BUKU 4 prefer to perform the defensive strategy on lending because they have various sources of income that not only depend on the loan. Finally, these findings are in line with policies that have been made by Financial Services Authority (FSA) regarding the categorization of the bank’s size based on owned core capital.JEL Classification: G20, G21, G40 DOI: https://doi.org/10.26905/jkdp.v23i4.3401